Research Note: Molecular and pathologic characterization of avian adenovirus isolated from the oviducts of laying hens in eastern Japan - Fletcher P. Del Valle (Poultry Science, 2020)
Cases of poor egg production were investigated in 2 layer farms from Ibaraki Prefecture in eastern Japan. To identify any microbial agents that may have caused the problem, necropsy, bacterial isolation, histopathology, and virus detection were performed. Members of the avian adenoviruses was detected by PCR in oviduct samples from both farms; chicken anemia virus coinfection was also confirmed in one of the farms. Avian adenovirus was isolated from the oviducts of the affected chickens on each farm. Inoculation into chick embryos showed tropism for the chorio-allantoic membrane. Stunting and hemorrhaging was observed in all infected embryos, as well as death in a few. Inoculation of 1-day-old specific pathogen-free chicks, and 400-day-old commercial hens, did not result in any significant findings. The isolated viruses were analyzed by sequencing of the hexon gene and were confirmed as fowl adenovirus type-c serotype-4 (FAdV-4). The 2 virus strains were found to be 99.29% similar to each other. One of the strains, Japan/Ibaraki/Y-H6/2016, was 99.15% similar to the KR5 strain. The other, Japan/Ibaraki/M-HB2/2016, was 99.57% similar to the KR5 strain. Fiber-2 gene analysis confirmed the identity as FAdV-4 that is closely related to nonpathogenic strains. Although nonpathogenic to chicks and laying hens, this infection can possibly cause economic damage. Perhaps the bigger concern is the effect on infected breeder operations. Because the virus is fatal to 9.09% of infected embryos, this could translate to a considerable loss in chick production owing to embryonic death. This is the first report of detection and isolation of FAdV-4 from the chicken oviduct; however, further studies are needed to elucidate its impact on both layer and breeder flocks. Indeed, FAdV-4 has negative effects on the avian reproductive tract as well.